FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PRAKTIK MENGKONSUMSI SOPI (MINUMAN ALKOHOLTRADISIONAL) PADA REMAJA DI DESA TAWIRI KECAMATAN TELUK AMBON KOTA AMBON - Lourens, Viona Milana Deasy (Fakultas Kesehatan Masyarakat, 2016)
Consumption of alcohol can be bad for health. WHO saidÂ 61% of the population worldwide consume alcohol. The prevalence of alcohol consumption in Indonesia 4.6%. Maluku province is ranked 6th nationally alcohol consumption with 8.2% prevalence, specifically the city of Ambon by 6.1%. Sopi is a traditional alcoholic beverage in Ambon city with a consumption rate of 62.5%. The purpose of this study to identify factors related to the practices sopi consumption (traditional alcoholic drink) on teenagers in the village Tawiri. The method used quantitative with cross sectional approach. The population in this study all adolescents aged 12-15 years in the village Tawiri and a sample of 84 people with simple random sampling technique. Analyzewere used univariate and bivariate with chi-square statistical test (level of significance 0.05). The practiceconsumesof sopi is 75%. The test results showÂ the variable related with sopi consumption practices are attitudes about the consume habits of sopi (p = 0.023), the availability of sopi (p = 0.0001), influence of family (p = 0.004), the influence of friends (p = 0.034). Meanwhile knowledge aboutÂ the impact of consumesopi and participation in traditional customs are not related in practice of sopi consumes. The conclusion of this study there arefactors relatedof sopi consumption practices are attitude,the availability of sopi,family and friends. While knowledge and participation in the indigenous traditionare not factors related of sopi consumption practices. Advice for teens are expected to avoid the consume habits of sopi.